Statycznie Dopuszczalne Pola Momentów Plastycznych dla Płyt - Gutkowski, W.; Szczepiński, W. (Engineering Transactions, 1971)
An exact determination of the limiting load capacity of plates having in plane composite shapes, and in particular of plates with discontinuous boundary conditions and perforated plates involves great difficulties. However, it is relatively easy to determine the lower estimate of limiting load capacity of such plates, subjected to pure bending, on the basis of the extreme theorems of the theory of plasticity. In this paper the concept of discontinuous statistically permissible limiting fields of moments is introduced both for plates with sandwich cross-sections and with compact cross-section. These fields are composed of regions subjected to uniform load, separated by the lines of discontinuity for the plasticity conditions of Treska and Huber-Mises. In the second part of the paper several examples are given for determining the lower estimate of the limiting load capacity of perforated plates and plates with discontinuous boundary conditions. Examples are also given of the optimalization of the spacing of holes in perforated plates.